Intermittent hypoxia conditioning as a potential prevention and treatment strategy for ischemic stroke: Current evidence and future directions - Yuan, Honghua; Liu, Jia; Gu, Yuhang; Ji, Xunming; Nan, Guangxian (Frontiers in Neuroscience, 2022)
Ischemic stroke (IS) is the leading cause of disability and death worldwide. Owing to the aging population and unhealthy lifestyles, the incidence of cerebrovascular disease is high. Vascular risk factors include hypertension, diabetes, dyslipidemia, and obesity. Therefore, in addition to timely and effective reperfusion therapy for IS, it is crucial to actively control these risk factors to reduce the incidence and recurrence rates of IS. Evidence from human and animal studies suggests that moderate intermittent hypoxia (IH) exposure is a promising therapeutic strategy to ameliorate common vascular risk factors and comorbidities. Given the complex pathophysiological mechanisms underlying IS, effective treatment must focus on reducing injury in the acute phase and promoting repair in the recovery phase. Therefore, this review discusses the preclinical perspectives on IH conditioning as a potential treatment for neurovascular injury and highlights IH pre and postconditioning strategies for IS. Hypoxia conditioning reduces brain injury by increasing resistance to acute ischemic and hypoxic stress, exerting neuroprotective effects, and promoting post-injury repair and regeneration. However, whether IH produces beneficial effects depends not only on the hypoxic regimen but also on inter-subject differences. Therefore, we discuss the factors that may influence the effectiveness of IH treatment, including age, sex, comorbidities, and circadian rhythm, which can be used to help identify the optimal intervention population and treatment protocols for more accurate, individualized clinical translation. In conclusion, IH conditioning as a non-invasive, non-pharmacological, systemic, and multi-targeted intervention can not only reduce brain damage after stroke but can also be applied to the prevention and functional recovery of IS, providing brain protection at different stages of the disease. It represents a promising therapeutic strategy. For patients with IS and high-risk groups, IH conditioning is expected to develop as an adjunctive clinical treatment option to reduce the incidence, recurrence, disability, and mortality of IS and to reduce disease burden.